The Influence of Gadgets on Child Growth and Development - Kusumaningtyas, Lydia (Research Horizon, 2024)
The study aims at finding out the bad influences of playing gadgets for the students at kindergarten school. The subject of the study is the parents of students of TK Lakshmi 7 Surakarta who are 13 people (50% of parents and two teachers are involved due to health protocols). The approach or solution of the problem is giving counselling about the effect of using gadgets in the growth and development of early childhood to the parents. After conducting the counselling, it turns out that all participants understand the material given. However, after field observations were carried out as a follow-up to the provision of materials, it was found that there was one parent (6.7%) who still gave gadgets on their children as a game, so it can be concluded that there are 93.3% of students who really master the material and implement it (13 parents of students and 2 teachers).